Mariátegui: marxismo y praxis indígena - Félix Pablo Friggeri (Universidad de los Andes, 2021)
Objective/Context: I present in this work some political and epistemic contributions of José Carlos Mariátegui to construct Latin American knowledge that contributes to the conformation of theories configured from the popular praxis of struggle for life, especially the indigenous one. Methodology: Based on the bibliographic analysis of this author and authors who work on Mariátegui, I seek to point out key elements of fruitful concepts by this author: heroic creation, Indo-American socialism, elements of practical socialism. I analyze the meaning of heroic creativity first and then its foundation in popular praxis, mainly indigenous. Conclusion: I dedicate a final section to some challenges for reflecting on Marxism from our popular realities and worldviews. Originality: I conclude by highlighting, from Amauta’s contribution, the importance of the Marxist contribution in the construction of revolutionary knowledge in our region, understanding it as necessary but not sufficient for this task.